Perempuan, Kemiskinan dan Anggaran Pembangunan - Indraswari Indraswari (Jurnal Administrasi Publik, 2008)
This paper discusses the relationship between poverty, gender and development budget. Poverty is a multidimensional phenomenon and it needs to be approached from various perspectives. Worldwide women constitute 70% of the poor while among the poor women are the poorest. In terms of development women are lack behind men in areas such as health and education. Therefore development budget should be gender sensitive and address women's specific needs.Keywords: gender, poverty, development budget.